Basophil Activation Test With Aspergillus Molecules: The Case for ABPA - Michel, Moïse; Sereme, Youssouf; Mankouri, Farid; Gouitaa, Marion; Gautier, Clarisse; Mège, Jean-Louis; Cassagne, Carole; Ranque, Stéphane; Reynaud-Gaubert, Martine; Vitte, Joana (Frontiers in Allergy, 2022)
Background. Allergic bronchopulmonary aspergillosis (ABPA) is an underestimated allergic disease due to Aspergillus fumigatus (AF). The main diagnostic criteria for ABPA rely on the evaluation of immunoglobulin (Ig) E and IgG responses to AF extracts, although these cannot discriminate AF-sensitization from ABPA. Objectives. To evaluate the performance of cellular functional assays with extract and molecular AF allergens in ABPA. Methods. A prospective cohort of 67 patients (6 ABPA) was investigated with basophil activation test (BAT) with AF extract. Nine patients were further investigated for BAT responses to molecular AF components: Asp f 1, Asp f 2, Asp f 3, Asp f 4 and Asp f 6. Results. BAT with AF extract with an optimized cutoff displayed 100% sensitivity and 77.6 % specificity for ABPA diagnosis. Among patients with positive BAT to AF, BAT with Asp f 4 was significantly higher in ABPA patients at 10 ng/mL (mean basophil stimulation index 10.56 in ABPA vs 1.24 in non-ABPA patients, p = 0.0002). Conclusion. BAT with AF is a promising diagnostic biomarker in the context of suspected ABPA, which can be further improved with AF molecular allergens, especially Asp f 4.